2012
DOI: 10.12681/mms.299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ecological quality status of Küçükçekmece Bay (Marmara Sea) by applying BENTIX, AMBI, BOPA and BO2A biotic indexes

Abstract: This study was carried out to explore the effectiveness of different biotic indexes in the Marmara Sea. The assessment of ecological quality status (EQS) was performed by applying the biotic indexes BENTIX, AMBI, BOPA, BO2A and Shannon-Wiener diversity, in combination with the estimation of total organic carbon (TOC) content of sediments. BOPA and BO2A indexes tended to overestimate the EQS of the stations. BENTIX was the most efficient index as it demonstrated conceivable EQS results with respect to TOC load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This ratio has proven especially effective to detect benthic disturbances in response to human pressures resulting from oil spills or offshore oil and gas production (e.g. Gomez and Dauvin, 2000;Nikitik and Robinson, 2003;Andrade and Renaud, 2011;Joydas et al, 2011Joydas et al, , 2012Sukumaran et al, 2013;Seo et al, 2014;Spagnolo et al, 2014), organic enrichment in sediments due to sewage discharge , 2012bVazirizadeh and Arebi, 2011;Subida et al, 2012;Pinedo et al, 2012;Serrano et al, 2014), fish farms (Keeley et al, 2012;Jahani et al, 2012;Karakassis et al, 2013;Zhang et al, 2013;Riera and de-laOssa-Carretero, 2013;Aguado-Giménez et al, 2015), organic and heavy metal contamination and diverse human activities (Dauvin et al, , 2012Munari and Mistri, 2007;Pranovi et al, 2007;Blanchet et al, 2008;Bakalem et al, 2009;Grimes et al, 2010;Pelin, 2011;Wetzel et al, 2012;Caglar and Albayrak, 2012;Saddik and Zourarah, 2013;Taupp and Wetzel, 2013), mosaic of habitats (Bouchet and Sauriau, 2008;Munari and Mistri, 2008;Lavesque et al, 2009;Do et al, 2011Do et al, , 2012Culhane, 2012), eutrophication (Afli et al, 2008;Zhang et al, ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ratio has proven especially effective to detect benthic disturbances in response to human pressures resulting from oil spills or offshore oil and gas production (e.g. Gomez and Dauvin, 2000;Nikitik and Robinson, 2003;Andrade and Renaud, 2011;Joydas et al, 2011Joydas et al, , 2012Sukumaran et al, 2013;Seo et al, 2014;Spagnolo et al, 2014), organic enrichment in sediments due to sewage discharge , 2012bVazirizadeh and Arebi, 2011;Subida et al, 2012;Pinedo et al, 2012;Serrano et al, 2014), fish farms (Keeley et al, 2012;Jahani et al, 2012;Karakassis et al, 2013;Zhang et al, 2013;Riera and de-laOssa-Carretero, 2013;Aguado-Giménez et al, 2015), organic and heavy metal contamination and diverse human activities (Dauvin et al, , 2012Munari and Mistri, 2007;Pranovi et al, 2007;Blanchet et al, 2008;Bakalem et al, 2009;Grimes et al, 2010;Pelin, 2011;Wetzel et al, 2012;Caglar and Albayrak, 2012;Saddik and Zourarah, 2013;Taupp and Wetzel, 2013), mosaic of habitats (Bouchet and Sauriau, 2008;Munari and Mistri, 2008;Lavesque et al, 2009;Do et al, 2011Do et al, , 2012Culhane, 2012), eutrophication (Afli et al, 2008;Zhang et al, ...…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that, in most cases, the BOPA and BO2A indices tended to overestimate the Ecological Status of the stations (e.g. Caglar and Albayrak, 2012;Reizopoulou et al, 2014;Aguado-Giménez et al, 2015), but the comparisons showed in most of the cited studies did not take into account the revised thresholds proposed by de-la-Ossa-Carretero and , including recent publications (Nebra et al, 2014;Aguado-Giménez et al, 2015). In addition, Keeley et al (2012) pointed out that the Ecological Status classification was underestimated by BOPA when the species richness and abundances of macro-invertebrates were very low, though the use of BOPA was not recommended for abundance <20 ind.…”
Section: Discussionmentioning
confidence: 99%
“…BENTIX is considered an ecologically relevant biological index, which is easier to operate than AMBI and M-AMBI and has been successfully applied to areas of organic matter pollution, oil spills, and heavy metal pollution (Simboura and Zenetos, 2002;Zenetos et al, 2004;Simboura et al, 2007). It is more sensitive to the increase in organic matter content in sediments than AMBI (Caglar and Albayrak, 2012), but all opportunistic taxonomic groups (AMBI-EG IV and V) and sensitive taxonomic groups (AMBI-EG III) are given the same proportion in the evaluation; therefore, the ecological state is easily underestimated. At the same time, unassigned organisms remain neglected because of their reliance on the AMBI classification criteria.…”
Section: Comparisons Among Different Biotic Indicesmentioning
confidence: 99%
“…Benthic indices have been extensively applied to assess the ecological quality of coastal regions worldwide, effectively gauging the impact of human activities on coastal ecosystem quality in numerous investigations [7]. For example, the multivariate AMBI (M-AMBI) is an effective index for assessing the ecological quality of the Sea of Japan [8], and the BENTIX is an effective index for assessing the ecological quality of the Marmara Sea [9]. Indices based on macrobenthos are commonly employed to evaluate the ecological quality of coastal areas globally.…”
Section: Introductionmentioning
confidence: 99%